THE GENDER CHARACTERISTICS OF ACCOCIATIVE UNITS IN DIFFERENT SISTEMATIC LANGUAGES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis explores the gender-specific characteristics of associative units in different systematic languages. It aims to analyze how male and female speakers perceive and respond to linguistic stimuli through associative reactions, reflecting cultural, psychological, and cognitive gender patterns. By comparing associative responses across languages such as English, Russian, and Uzbek, the study highlights semantic, emotional, and metaphorical tendencies characteristic of each gender group. The research also investigates how societal gender roles, stereotypes, and national worldviews influence the formation and use of associative meanings. The findings contribute to the fields of gender linguistics, psycholinguistics, and intercultural communication, offering a deeper understanding of how gendered cognition is encoded in language.